IMPROVING STUDENTS’ VOCABULARY BY USING JAZZ CHANTS - Ambarwati, Penny; ., Regina; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The aim of this Classroom Action Research was to improve the third grade students' vocabulary at SD Negeri 07 Pontianak. This research consisted of two cycles. The subjects of the study were 30 students of third grade of SD Negeri 07 Pontianak in the academic year of 2012/2013. To collect data, the writer used achievement test and observation checklist. To analyze the finding data, the writer used descriptive method where the researcher describes all the processes of vocabulary teaching and learning process using Jazz chants. In cycle 1 the students' score of vocabulary did not achieve the minimum level of achievement (MLA) 65, where the students' score was 50.83. By having these result, the writer then re-conducted the next cycle. In the cycle 2, the student's vocabulary improved, where the students' score was 89.30. By having this result, the students' vocabulary also achieved the MLA. It means that Jazz Chant was appropriate to be applied to improve students' vocabulary. Keywords: Vocabulary, Jazz Chants Abstrak: Tujuan penelitian tindakan kelas ini adalah untuk meningkatkan kosakata siswa kelas 3 SD Negeri 07 Pontianak. Penelitian ini terdiri dari dua siklus. Subjek penelitian ini adalah 30 siswa kelas 3 SD Negeri 07 Pontianak tahun pembelajaran 2012/ 2013. Untuk mengumpulkan data, peneliti menggunakan uji kemampuan dan lembar observasi. Untuk menganalisa data, peneliti menggunakan metode deskriptif dimana peneliti menggambarkan semua proses belajar mengajar kosakata menggunakan Jazz Chants. Di siklus I nilai siswa tidak mencapai standar pencapaian minimal 65, nilai kosakata siswa 50,83. Dengan hasil ini, peneliti lalu melanjutkan ke siklus berikutnya. Dalam siklus ke II, nilai kosakata siswa meningkat menjadi 89,30. Dengan hasil ini, kosakata siswa telah mencapai nilai pencapaian minimal. Ini menunjukkan bahwa Jazz chants cocok untuk diaplikasikan untuk meningkatkan kosakata siswa. Kata Kunci: Kosakata, Jazz Chants